Legal Counselling on Legal Awareness at LPKA Class I Tangerang - Rila Kusumaningsih (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Legal counselling at LPKA fostered law awareness, boosting residents' understanding and compliance. The approach was educational. It provided participants with better knowledge of legal rights and duties. It also led to a more positive attitude towards laws and regulations. The extension program used an educational approach. It involved lectures, group talks, and legal case simulations. The materials included an introduction to legal rights and duties. Also, the legal outcomes of crimes. And, the role of ethics and morals in daily life. Counselling participants joined discussions. They also did activities and grasped legal concepts. The program also developed the participants' ability to avoid unlawful behavior. This is an important step in their reintegration into society. The program evaluation showed that participants had a big increase in legal awareness. They also had better behavior. This should help coaching succeed. It will also reduce kids' and teens' re-offending at LPKA